Effect of exotic tree plantations on plant diversity and biological soil fertility in the Congo savanna: with special reference to eucalypts - Bernhard-Reversat, F. (Center for International Forestry Research, 2001)
In the southern coastal region of Congo near Pointe-Noire, savanna covers large areas on very poor sandy soils. These savannas have been used since 1978 for plantations of fast growing trees, mainly eucalypts, which are grown commercially. A particular feature of the Congolese plantations was their establishment on savanna with poor soil and vegetation. This document reports a study on the importance of the biological factors in fertility. The report is divided in three parts: (i) The effect of both savanna and forest on undergrowth colonisation, and the trends of understorey vegetation changes with age. (ii) The relationships between vegetation and fertility are closely linked to litter and soil organic matter quality and quantity these were studied in an age series of eucalypt hybrids and clones. (iii) The density of the main taxa of macrofauna and nematodes was assessed according to the age of plantation and logging. Nitrogen fixation ability related to the dramatic N shortage expected to occur in aging plantations was also studied. In the harsh environment like the Congolese savanna, silviculture is a land use that has numerous positive effects although there are many problems still to be addresed. The increase in soil organic matter accounts for many positive changes is a fragile process. All management practices likely to decrease inputs, such as the burning of harvest residues, the harvest of twigs and leaves for fuel, and the harvest of logs with the bark, are expected to counteract environmental improvements resulting from eucalyptus growth. The choice of species and hybrids beside their growth and wood qualities should take into account litter quality and decomposition rate. Further research is needed on the cumulative effect of silvicultural practices involved in short-rotation forestry and its relation with soil organic matter. (YS)